A prenatal group based phone counseling intervention to improve breastfeeding rates and complementary feeding: a randomized, controlled pilot and feasibility trial - Jennifer S. Cauble; Amy Herman; Jo Wick; Jeannine Goetz; Christine M. Daley; Debra K. Sullivan; Holly R. Hull (BMC, 2021)
Abstract Background Despite numerous benefits for both mom and baby, few infants are exclusively breastfed for the recommended first six months. Additionally, infants are given solids too early. Prenatal education increases rates of breastfeeding initiation and we hypothesize it can also improve exclusive breastfeeding rates and prevent the early introduction of solids. We conducted a randomized controlled pilot and feasibility trial to understand the feasibility and maternal acceptance of a prenatal behavioral lifestyle intervention (PBLI) delivered via group based phone counseling (GBPC) and its effectiveness on rates of exclusive breastfeeding up to six months postpartum. Secondary aims included rates of any breastfeeding up to six months, rates of early introduction of solids, and infant feeding progression. Methods Forty-one pregnant women were recruited from a Kansas City Metropolitan Obstetrics and Gynecology office and randomly assigned to a usual care group or a PBLI. Women in the PBLI participated in six GBPC sessions where they learned about breastfeeding and introducing solids. Feeding questionnaires to assess breastfeeding and introduction of solids were sent at two weeks, two months, four months, and six months postpartum. Structured interviews were also conducted after the intervention and at six months postpartum to assess maternal acceptance and intervention feasibility. Results Participants overwhelmingly found the intervention acceptable and beneficial. Rates of exclusive breastfeeding and any breastfeeding did not differ between groups at any time point. No between group differences were found for early introduction of solids or infant feeding progression. Conclusions Mothers discontinue breastfeeding earlier than recommended despite high rates of initiation. A PBLI delivered via GBP is feasible, acceptable to participants, and showed positive impacts such as maternal empowerment for both breastfeeding and introducing solids. Future interventions should incorporate both prenatal and postpartum components. Trial registration Study protocols were approved by the University of Kansas Medical Center's Human Subjects Committee (STUDY00140506) and registered at ClinicalTrials.gov on 02/22/2018 ( NCT03442517 , retrospectively registered). All participants gave written informed consent prior to data collection.